Gårdsbaserad uppgradering av biogas med askfilter - Hävermark, Ulf (2017)
Most of the biogas produced in small scale biogas plants in Sweden today is used for combined heat and power production. With the price of electricity being relatively low, the small biogas plants are hardly profitable. Since the electricity in Sweden is largely renewable the environmental motivation for farmers to build their own small scale biogas plants is low. If the biogas could be used as vehicle fuel instead this might change. Vehicle fuel is still mostly fossil which means that production of small scale vehicle fuel would benefit both the environment and the producers. The problem however is that upgrading small flows of biogas is too expensive with todays established technologies.